Specific risks of false decisions in conformity assessment of a substance or material with a mass balance constraint – A case study of potassium iodate. (March 2021) - Pennecchi, Francesca R.; Kuselman, Ilya; Di Rocco, Aglaia; Brynn Hibbert, D.; Sobina, Alena; Sobina, Egor
Graphical abstract: Total specific consumer's risk R c ∗ (a) and producer's risk R p ∗ (b) in dependence on measured directly purity c 1mD and impurities content c 2mD . Highlights: Specific risks in a material conformity assessment are studied at a mass balance constraint. A Bayesian evaluation of total specific risks due to measurement uncertainty is developed. A Monte Carlo method taking into account the mass balance constraint is applied. Specific risks in the assessment of a potassium iodate purity are evaluated as a case study. Abstract: A methodology for the Bayesian evaluation of total specific risks of false decisions on conformity of a substance or material due to measurement uncertainty was developed using Monte Carlo simulations, taking into account the mass balance constraint of the data. As a case study, the measurement results (measured values and associated measurement uncertainty) obtained for testing a potassium iodate batch, being considered as a candidate reference material of potassium iodate purity, were analyzed and discussed for different models of the prior probability density function and the likelihood function. Different scenarios of the risks related to determination of potassium iodate purity were studied, when the direct or indirect test method is applied, as well as when both are used simultaneously.